NORTH-SOUTH RELATIONS IN CONDUCTONG THE CONCEPT OF "SUSTAINABLE DEVELOPMENT" - Loong, Ying Shao (Global: Jurnal Politik Internasional, 2002)
This paper traces the debate over sustainable development between North countries and the Southern ones. Each side has its own interest regarding the issue of development, therefore conflicts are common among them. The Northern, along with its past achivement in development, is considered the lucky side. The idea of development is derived from their centuries-long experience. Thus, development is a bias term used to adopt the way of the Northern thinking regarding progress. The Southern is at the unfortunate side to follow the path considered righteous but at the same time forced to deal with dualist attitude of the North when it comes with the later's exclusively domestic interest. In the face of sustainable development, the Nortern countries can be a very pressing actor for the Southern to obey with its principles. Their centuries-late way of production is the target of environmentalist argument from the North related to the waste it creates. But these lucky countries can swing fast when their national industries are challenged by environmentalist argument from the South.